The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1017/s0022112096000699
|View full text |Cite
|
Sign up to set email alerts
|

Simple cases of the streamline-curvature instability in three-dimensional boundary layers

Abstract: A new instability of the centrifugal type due to the curvature of external streamlines was theoretically predicted in a recent study on boundary layers along a swept wing. It is, however, not clear how this instability relates to already-known instability phenomena in various three-dimensional flows. So the basic idea developed in the analysis of boundary layers is applied to the simpler problems of the flow on a rotating disk and along the leading edge of a yawed circular cylinder, and the resulting eigenvalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
1
37
1
Order By: Relevance
“…4−8 In the flow on a rotating disk, the S-C instability has a very low critical Reynolds number and is amplified upstream of the critical point of C-F mode. 6 On the other hand, Takagi et al 9 and Takagi and Itoh 10 have observed that amplified S-C disturbances directly influence spatial growth rate of C-F mode. It is also observed that strongly amplified S-C mode leads to another route of transition that is different from the usual process governed by C-F streamwise vortices.…”
Section: Nomenclaturementioning
confidence: 99%
“…4−8 In the flow on a rotating disk, the S-C instability has a very low critical Reynolds number and is amplified upstream of the critical point of C-F mode. 6 On the other hand, Takagi et al 9 and Takagi and Itoh 10 have observed that amplified S-C disturbances directly influence spatial growth rate of C-F mode. It is also observed that strongly amplified S-C mode leads to another route of transition that is different from the usual process governed by C-F streamwise vortices.…”
Section: Nomenclaturementioning
confidence: 99%
“…It is also deduced that the cross-flow instability of three-dimensional boundary layers is not greatly affected by the nonparallelism of order R −1 , because this instability is of an inviscid inflection-point type. However the streamline-curvature instability, recently found to occur in three-dimensional boundary layers, [3][4][5] is of centrifugal type due to the curvature of external streamlines; therefore it cannot be described by the O-S equation, which ignores curvature effects of the nonparallel terms.…”
Section: Introductionmentioning
confidence: 99%
“…This equation consists of the parallel-flow approximation plus some additional terms associated with the modified vertical velocityŴ of the basic flow; that is, a neglect of theŴ terms yields the Orr-Sommerfeld equation, and the additional terms given here may be considered to represent the most important nonparallel effects on stability characteristics of boundary-layer flows, as previously pointed out by the author. 8) The boundary conditions to be imposed on the disturbance velocity w are given by…”
Section: Basic Flow and Linear Stability Equationsmentioning
confidence: 99%